STRENGTHENING THE STATE DEFENSE SYSTEM OF THE REPUBLIC OF INDONESIA THROUGH IMPLEMENTATION OF THE STATE DEFENSE POLICY - Hermina Manihuruk (Yogyakarta State University, 2020)
Defending the state is the attitude and actions of citizens based on love for the country, awareness of the nation and state, belief in Pancasila as the ideology of the nation and state, willingness to sacrifice to face threats, challenges, obstacles, and disturbances (ATHG). To achieve national goals, the Astra gatra composing National Resilience requires an integrated implementation system that refers to geopolitical dynamics. This integrated system can be stated in a state defense system that already has a strong legal basis in the 1945 Constitution, as well as Law Number 3 of 2002 concerning State Defense (Law No. 3/2002), Article 9 of Law Number 3 of 2002. Law -The State Defense Law also classifies state defense into three groups, namely the Main Component (TNI), Reserve Component, and Supporting Component. In implementing state defense, a citizen can do it both physically and non-physically. Physical state defense includes struggling to take up arms when there is an attack from a foreign country against national sovereignty. Thus, it is necessary to further study the implementation of existing policies regarding state defense, as an effort to strengthen the state defense system of the Republic of Indonesia. In this writing using qualitative research methods.